Synthesis and characterization of clay-based catalysts prepared from natural clays - Silva, Adriano S. (2020)
This work deals with the synthesis and characterization of clay-based catalysts. The catalysts prepared in this work were clays activated through acid treatment and clays pillared with Co and Fe. For the preparation, natural clays from four different regions of Kazakhstan were used: Akzhar, Asa, Karatau and Kokshetau. The FTIR analysis showed that the pillared clays have an amount of iron in its structure. The N2 adsorption isotherms obtained were classified as Type II, according to IUPAC classification, typical of macroporous materials. The SBET calculated with the N2 adsorption isotherms for the activated clays showed to be higher than the SBET results for natural clays. XRD patterns helped to gather information about crystalline phases of the clay, allows classifying the type of clay used in the work. The acid characterization showed that the procedures used for the preparation of the acid activated clays and pillared clays caused structural modifications, which is another result that suggests the success of both methods.